Developmental dyslexia intervention framework for speech therapists - Jiménez-Fernández, Gracia; Defior, Sylvia (Revista de Investigación en Logopedia, 2014)
The aim of this paper is to provide an intervention framework for speech therapists for developmental dyslexia in an educational environment. Firstly, there is a list of the main aspects which should be included in the individual intervention, such as reading fluency, phonological abilities and, in most cases, reading comprehension. The collaboration between teacher and speech therapist is essential in order for the child to overcome this learning difficulty. In this sense, in addition to the individual intervention, the speech therapist’s role also includes offering orientations for the intervention in the classroom. For this reason, secondly, this article presents some recommendations which the speech therapist can give to the teacher who has students with this learning disability. Among them, there are included some adaptations which can be carried out whilst doing daily tasks and for exams, as well as the intervention for emotional aspects which may be affected, such as selfesteem.